2015
DOI: 10.1017/s0021859615000441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil zinc availability, nitrogen fertilizer rate and zinc fertilizer application method on zinc biofortification of rice

Abstract: SUMMARYRice (Oryza sativa L.) is one of the most important cereal crops in the world and a potentially important source of zinc (Zn) in the diet. The improvement of Zn content of rice is a global challenge with implications for both rice production and human health. The objective of the present study was to identify the effects of nitrogen (N) fertilizer rates and Zn application methods on Zn content of rice by evaluating rice production on native soils with different Zn availabilities in 2010/11. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 53 publications
(84 reference statements)
2
47
0
2
Order By: Relevance
“…This might be related to the low DTPA-Zn levels in soil, indicating that Zn deficiency was a growth-limiting factor on the experimental soils as Cakmak et al (2010) and Gomez-Coronado et al (2016) found in soils with less of 0.3 mg DTPA-Zn kg -1 . Foliar Zn application had not any positive effect on grain yield, in contrast of Karim et al (2012) who found an improvement on growth and antioxidative defence mechanisms of plants against drought-induced oxidative cell damage under drought conditions with foliar Zn sprays but according with Cakmak et al (2010), Gomez-Coronado et al (2016) and Guo et al (2016). The higher grain yield found in both Soil + Foliar treatments and in some cultivars could produce a possible dilution effect.…”
Section: Discussionmentioning
confidence: 77%
“…This might be related to the low DTPA-Zn levels in soil, indicating that Zn deficiency was a growth-limiting factor on the experimental soils as Cakmak et al (2010) and Gomez-Coronado et al (2016) found in soils with less of 0.3 mg DTPA-Zn kg -1 . Foliar Zn application had not any positive effect on grain yield, in contrast of Karim et al (2012) who found an improvement on growth and antioxidative defence mechanisms of plants against drought-induced oxidative cell damage under drought conditions with foliar Zn sprays but according with Cakmak et al (2010), Gomez-Coronado et al (2016) and Guo et al (2016). The higher grain yield found in both Soil + Foliar treatments and in some cultivars could produce a possible dilution effect.…”
Section: Discussionmentioning
confidence: 77%
“…This effect could be due to the fact that Zn acts as a co‐factor for numerous enzymes involved in the metabolism of carbohydrates, proteins and auxins, in membrane integrity, and in flowering and seed production . Various authors have reported increases in the yields of different crops, such as wheat, maize, safflower and rice, with Zn fertilization. In a field experiment using barley as the test plant, Arora and Singh obtained the highest grain and straw yields with the application of 7.5 kg Zn ha −1 and 90 kg N ha −1 ; these yields were not, however, significantly different from those obtained with the application of 7.5 kg Zn ha −1 and 60 kg N ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the application of Zn to soils can serve as a tool of the agronomic biofortification of crops . Increasing the Zn concentration in grain is therefore a challenge with significant implications for barley production and the nutritional quality of grain …”
Section: Introductionmentioning
confidence: 99%
“…Each method has the potential to influence the extent of micronutrient concentration both in the treated plant directly and indirectly through enrichment of the seeds by micronutrient treatment of the parent (Johnson et al, 2005). Much of the research on crop responses to foliar fertilization was done on soybean (Glycine max L.), wheat (Triticum aestivum L.) (Fageria et al, 2009) and rice (Oryza sativa L.) (Guo et al, 2016) with only limited studies on chickpea. Foliar Zn application increased grain and straw Zn concentration in chickpea (Pathak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%